FASHION SEBAGAI MEDIA KOMUNIKASI ARTIFAKTUAL DALAM PEMBENTUKAN IDENTITAS SOSIAL MAHASISWI UNSAM LANGSA - Cut Nia Cinde (Yayasan Formadana Tabagsel Indonesia, 2025)
Fashion or clothing is anything worn on the body that can cover or protect the body and can characterize someone who wears the fashion. Fashion can not only be used to beautify the body but also as a media symbol to convey messages to the audience. The purpose of this research is to find out fashion as an artifactual communication media in the formation of social identity of UNSAM Langsa female students and to find out the relationship between fashion and social identity formation. This study uses qualitative research with the type of field research and in this study using data collection techniques using observation, interviews and documentation techniques. The population in this study UNSAM Langsa female students majoring in history education amounted to 273 people. The sampling technique in this study used snowball sampling technique, therefore this study took a sample of 5 female students majoring in history education. The results showed that fashion can describe a person's self through the fashion they wear and can also describe the social identity of the person who wears the fashion. However, not all things fashion can describe a person's self because some of them only consider fashion as a hobby.